PENGEMBANGAN MEDIA PEMBELAJARAN INDIKATOR ASAM BASA ALAMI BERBASIS BIOSELULOSA - Fhany Maulika; Rizmahardian Ashari Kurniawan; Dedeh Kurniasih (Jurnal Ilmiah Ar-Razi, 2019)
This study was motivated by the absence of the practicum activities, especially the acid-base indicator learning media, in several schools such as SMA Adisucipto Sungai Raya, SMAN 2 Sungai Raya and MAS Al Mustaqim. This problem is caused by the limited school facilities. For this reason, learning media is required to facilitate the practicum class. This study aimed to determine the validity and practicality of Bioselulose-based natural acid base media. This study used an ADDIE model of four stages ; Analysis, Design, Develop, and Implementation. As many as ten Chemistry teachers from Senior High Schools in Kecamatan Sungai Raya participated in this study. The sample was selected by using purposive sampling technique, and the schools were chosen based on the availability of the material, accessibility of the location, and the school accreditation. Data collection techniques and tools used indirect communication, questionnaires and validation sheets. The results of the validity analysis showed that an average of 0.92 with a very valid category, which meanth that the media was suitable to be used in the learning process. The results of the practicality showed an average of 95 with a very practical category. Therefore, the Biocelullose-based natural acid base media was valid, practical, and suitable for the practicum class in schools.